Attitudes of Malaysian university students towards accented english - Ahmed, Zainab Thamer (2016)
In the field of sociolinguistics, the exploration of second language learners’ attitudes towards language and language varieties seems to be very significant. Language attitude studies have generally indicated that second language learners preferred either American or British accents in their daily interaction. In the Malaysian context, there is a lack of information regarding the university students’ attitudes towards accented English and it is still unclear which variety of English the L2 learners tend to use as a model for their learning. This study investigated the attitudes of Malaysian university students towards six native and non-native varieties of accented English, including American, Australian, British, Chinese, Indian and Malay. Besides, the present study aimed at exploring whether respondents’ social factors exert any influence on their attitudes towards native and non-native varieties of accented English in terms of gender, ethnicity, ethnic identity, regional provenance, self-perceived proficiency in English, and identification of different accents. Based on a Multistage sampling procedure, a total of 1465 undergraduate local students in two Malaysian public universities were selected as respondents of the study. The respondents mostly belonged to three main ethnic groups, namely the Malays, Chinese, and Indians all comprising the Malaysian society. The present study also employed three cross validated research instruments, namely, a survey questionnaire, the verbal-guise technique, and focused group interviews in order to measure direct and indirect attitudes. These instruments have been previously employed in the related studies in fields of social psychology, folk linguistics, and sociolinguists in order to measure attitudes. Social Identity Theory (SIT) and Similarity Attraction Theory (SIT) were utilized to guide this study. The results of quantitative analysis showed that, in general, respondents preferred native varieties of accented English more than those of non-native based on status and solidarity dimensions. In addition, differences in the Malaysian respondents’ regional provenance, gender, levels of self-perceived proficiency in English, levels of accent identifications, and levels of ethnic identity all had significant effects on the learners’ attitudes towards accented English. However, the ethnicity of the respondents was not found to be a significant factor in determining their attitudes towards accented English. The results of qualitative analysis indicated that respondents also preferred native varieties of accented English than those of nonnative. On the other hand, when it came to teaching English at the university level, informants favored a combination of both native and non-native speakers of English to teach them, because each group of lecturers has its own capabilities and advantages. Additionally, non-native English lecturers should be given chances to train overseas to enhance their own English proficiency level and that only experienced native lecturers should be employed to teach English in Malaysian universities. The findings of this study have implications in relation to the choice of a pronunciation model in English language teaching (ELT) context. Additionally, applied linguists, policy makers, sociolinguists, and educators will also benefit from the results of the study as they have always been concerned about the language learners’ attitudes toward language and accent variation in order to fully address their needs and goals.